The rise of continuous packaging : understanding and securing software supply chains in the cloud - McKinney, Dan; Carey, Ciara (O'Reilly Media, Inc., 2022)
How packages are built, sourced, and integrated is vital to efficient and secure supply chains. Complete control over packages, from provenance to deployment, is critical for security during the software development lifecycle. As recent breaches attest, securing your software supply chain is now more critical than ever. What can you do? Simple package management strategies are not enough. You need a single source of truth for dependencies that you consume and artifacts you create. And you need to own the process of packaging your software artifacts, all the way from build to deployment and delivery. You need a global hub of trusted software. That's where continuous packaging (CP) comes in. In this report, you'll learn how CP gives your teams security, control, visibility, and management over incoming and built assets. You will: Understand how CP helps to secure a supply chain Learn what continuous packaging is and why it's crucial to CI/CD pipelines Discover software supply chain risks and their solutions Define strategies to mitigate those risks Identify the ways continuous packaging helps secure software development.